Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1017/s0142716419000250
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic interdependence of receptive vocabulary skills in emergent bilingual preschool children: Exploring a factor-dependent approach

Abstract: This study investigates the extent to which internal and contextual factors moderate the linguistic interdependence between receptive vocabulary skills in emergent bilingual children. Such factors are frequently related to first (L1) and second language (L2) skills, but few studies have examined their concurrent influence on the cross-language relationship, or have linked the results to the two main explanatory models for interdependence: common underlying proficiency or individual differences. Using a cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 78 publications
(173 reference statements)
2
15
0
1
Order By: Relevance
“…A possible explanation is that children's intelligence moderated language learning, since it was shown that children with higher intelligence scores were more likely to be assigned to the more favourable profile. More specifically, children with a higher general learning potential, as indicated by higher intelligence, may have learned more from language input at home and may have been better able to transfer conceptual knowledge and communicative competence to the second language than children with lower learning potential (see Sierens et al, 2019, for a discussion on linguistic interdependence theories and the role of language learning abilities). Finally, family SES was to a lesser extent associated with the profiles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation is that children's intelligence moderated language learning, since it was shown that children with higher intelligence scores were more likely to be assigned to the more favourable profile. More specifically, children with a higher general learning potential, as indicated by higher intelligence, may have learned more from language input at home and may have been better able to transfer conceptual knowledge and communicative competence to the second language than children with lower learning potential (see Sierens et al, 2019, for a discussion on linguistic interdependence theories and the role of language learning abilities). Finally, family SES was to a lesser extent associated with the profiles.…”
Section: Discussionmentioning
confidence: 99%
“…The findings regarding profile 3, the Dominant L1 use, relatively high L1 and L2 proficiency profile, seem to indicate that a high quantity of L1 exposure, assuming that the exposure is also of sufficient quality, can contribute to higher L1 and L2 proficiency, possibly through positive transfer (Cummins, 2008; Leseman et al, 2019). More research is needed to identify the mechanisms that underly positive transfer between languages, such as quantity and quality of language input (Prevoo et al, 2015; Sierens, Slembrouck, Van Gorp, Agirdag & Van Avermaet, 2019; Verhoeven, Voeten & Vermeer, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Studies increasingly examine the role of contexts of language learning in linguistic interdependence (Prevoo et al, 2016; Sierens, Slembrouck, Van Gorp, Agirdag, & Van Avermaet, 2019). As noted above, this study was partially motivated by the hypothesis that for Spanish-English bilinguals in DLI, stronger linguistic interdependence may emerge between cross-disciplinary ALs because students have been simultaneously socialization into Spanish-speaking and English-speaking academic discourse communities (Chung et al, 2018; Halliday, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…LIH according to Genesee, Geva, Kamil (2006, in Chung, Chen, &Geva, 2018, p.10) is very broad in perspective since it cannot predict how far a construct can transfer. According to Sierens, Slembrouck, Van Gorp, Agirdag, and Van Avermaet, (2019) the LIH does not apply to all areas of language. Cobo-Lewis, Pearson, Eilers, and Umbel ( 2002) also stated that interdependence between languages is affected by factors such as the type of skills being assessed.…”
Section: Discussionmentioning
confidence: 99%